Renovascular hypertension due to bilateral renal stenosis Right aortorenal: right aortorenal By-Pass - Delgado, Bolívar; Bonavita, Luis A; Piñeyro, Juan (Cirugía del Uruguay, 1973)
We present one case of renovascular hypertension reveloped as a consequence of bilateral renal stenosis, so that it can be added to national case material. Treatment consisted of right aortorrenal by-pass ,it was successful.